Management of collar rot disease in chili by farmyard manure and commercial biofertilizers - Sana, Nighat; Shoaib, Amna; Javaid, Arshad (Penerbit Universiti Kebangsaan Malaysia, 2017)
Collar rot of chili (Capsicum annuum L.) is a very destructive disease caused by a soil-borne fungal pathogen Sclerotium rolfsii Sacc. Generally, chemical fungicides are used to combat the menace but this practice is being discouraged because of health and environmental concerns. In the present study, an alternative environment friendly strategy was used to manage this disease by using farmyard manure (FYM) and two commercial biofertilizers namely Biopower and Feng Shou. S. rolfsii inoculated pot soil was amended with 1% and 2% FYM and the two commercial biofertilizers. Inoculation of soil with S. rolfsii only (positive control) resulted in the highest disease incidence (73%) and plant mortality (60%). Biopower and Feng Shou application reduced disease incidence to 20% and 7%, respectively and plant mortality to 0%. Likewise, 1% and 2% FYM amendment reduced disease incidence to 33% and plant mortality to 26% and 7%, respectively. Under biotic stress of S. rolfsii, FYM and biofertilizers applications, either alone or in combination, significantly enhanced root and shoot growth over positive control. S. rolfsii inoculation significantly increased peroxidase and polyphenol oxidase activities in chili plants which were further increased by application of either of the two biofertilizers. The present study concludes that biofertilizers Biopower and Feng Shou alone or in combination with 2% FYM can be effectively utilized to manage southern blight of chili.